Interaction with Tsg101 Is Necessary for the Efficient Transport and Release of Nucleocapsids in Marburg Virus-Infected Cells - Dolnik, Olga; Kolesnikova, Larissa; Welsch, Sonja; Strecker, Thomas; Schudt, Gordian; Becker, Stephan (PLoS pathogens, 2014)
Endosomal sorting complex required for transport (ESCRT) machinery supports the efficient budding of Marburg virus (MARV) and many other enveloped viruses. Interaction between components of the ESCRT machinery and viral proteins is predominantly mediated by short tetrapeptide motifs, known as late domains. MARV contains late domain motifs in the matrix protein VP40 and in the genome-encapsidating nucleoprotein (NP). The PSAP late domain motif of NP recruits the ESCRT-I protein tumor susceptibility gene 101 (Tsg101). Here, we generated a recombinant MARV encoding NP with a mutated PSAP late domain (rMARV(PSAPmut)). rMARV(PSAPmut) was attenuated by up to one log compared with recombinant wild-type MARV (rMARV(wt)), formed smaller plaques and exhibited delayed virus release. Nucleocapsids in rMARV(PSAPmut)-infected cells were more densely packed inside viral inclusions and more abundant in the cytoplasm than in rMARV(wt)-infected cells. A similar phenotype was detected when MARV-infected cells were depleted of Tsg101. Live-cell imaging analyses revealed that Tsg101 accumulated in inclusions of rMARV(wt)-infected cells and was co-transported together with nucleocapsids. In contrast, rMARV(PSAPmut) nucleocapsids did not display co-localization with Tsg101, had significantly shorter transport trajectories, and migration close to the plasma membrane was severely impaired, resulting in reduced recruitment into filopodia, the major budding sites of MARV. We further show that the Tsg101 interacting protein IQGAP1, an actin cytoskeleton regulator, was recruited into inclusions and to individual nucleocapsids together with Tsg101. Moreover, IQGAP1 was detected in a contrail-like structure at the rear end of migrating nucleocapsids. Down regulation of IQGAP1 impaired release of MARV. These results indicate that the PSAP motif in NP, which enables binding to Tsg101, is important for the efficient actin-dependent transport of nucleocapsids to the sites of budding. Thus, the interaction between NP and Tsg101 supports several steps of MARV assembly before virus fission.